Segni di inciviltà sul territorio e “paura” del crimine - Moris Triventi (Quaderni di Sociologia, 2008)
The aim of this paper is to study the relation between citizens’ perception of social incivilities and fear of crime. In the first part I review several theories and hypotheses within the ecological perspective, especially focusing on the incivilities and the “broken windows” theories. In the second part, I present several ways to operationalize and measure the concepts of incivilities and fear of crime, discussing their advantages and shortcomings. In the third part, I analyse data from the Italian Survey on Citizens’ Safety (Istat, Indagine sulla sicurezza dei cittadini). The analysis demonstrates that there is a positive relation between the observation of incivilities and fear of crime. Regression models show that people who often see incivilities in their own residence area are more likely to feel unsafe when they are walking alone in the streets in the night and they perceive their area as more unsafe, all else being equal. This relation is stronger in metropolitan areas than in small and medium size communities. On the contrary, the perception of incivilities decreases the probability of going out in the night only among women.